European Parliament election study 2004 - Holmberg, Sören; Ekengren Oscarsson, Henrik; Statistics Sweden (University of Gothenburg, 2014)
The third Swedish election to the EU-parliament was held on the 13th of June 2004. As in connection to all general elections and referenda held in Sweden since 1956, an election study was carried out in connection to this election. The main subject of the survey was the European Union and the respondent´s attitudes toward the Swedish EU membership, but the survey also included a number of questions asked in one or several of the Swedish election studies.

Purpose:

Explain why people vote as they do and why an election ends in a particular way. Track and follow trends in the Swedish electoral democracy and make comparisons with other countries.

Det tredje svenska valet till EU-parlamentet hölls den 13 juni 2004. Liksom vid alla allmänna val och folkomröstningar hållna i Sverige sedan 1956 genomfördes en valundersökning i samband med detta val. Det huvudsakliga ämnet för undersökningen var Europeiska unionen och respondenternas inställning till det svenska EU-medlemskapet, men undersökningen innehåller även ett antal frågor som ställts i en eller flera av de tidigare svenska valundersökningarna.

Syfte:

Förklara varför väljare röstar som de gör och varför val slutar som de gör. Spåra och följa trender i svensk valdemokrati och göra jämförelser med utvecklingen i andra länder.
Europaparlamentsvalundersökning 2004
Keywords: elections; val; european union; europeiska unionen; european integration; europeisk integration; european parliament; europaparlamentet; single european currency; gemensam europeisk valuta; internal politics; inrikespolitik; election campaigns; valkampanjer; electoral issues; valfrågor; european parliament elections; europaparlamentsval; CORS; CORS; Political behaviour and attitudes; Politiska beteenden och attityder; Elections; Val; Government, political systems and organisations; Regering, politiska system och organisationer; International politics and organisations; Internationell politik och organisationer; Social Sciences; Samhällsvetenskap; Political Science; Statsvetenskap